GERAKAN GEMAR MENABUNG SEJAK DINI MELALUI PROYEK KREATIF PEMBUATAN CELENGAN DI KELAS II SD N170/VI DESA RASAU - Samsiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to foster a habit of saving from an early age among second-grade students at SDN 170/VI in Rasau Village through a creative piggy bank-making project. The study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, implemented over several cycles, including the planning, implementation, observation, and reflection stages. The study sample consisted of 20 students. Data collection techniques included observation, questionnaires, interviews, and documentation. The results showed a significant improvement in students’ understanding of and habits regarding saving. Before the intervention, only 40% of students understood the importance of saving, and 30% had a habit of saving. After the intervention, these figures increased to 90% and 85%, respectively. Additionally, piggy bank ownership increased to 100%, and the habit of setting aside allowance money reached 80%. This activity also enhanced students’ creativity, learning motivation, as well as their discipline and sense of responsibility. Thus, the creative piggy bank-making project proved effective as an innovative learning method for instilling financial literacy from an early age while simultaneously developing the cognitive, affective, and psychomotor aspects of elementary school students.